The fantastic undersea life of Jacques Cousteau [videorecording (DVD)] - Yaccarino, Dan; Marshall, Qarie, 1970- (Dreamscape, 2014)
Jacques Cousteau was the world's ambassador of the oceans. His popular TV series brought whales, otters, and dolphins right into people's living rooms. From the first moment he got a glimpse of what lived under the ocean's waves, Cousteau was hooked. And so he set sail aboard the Calypso to see the sea. He and his team of scientists invented diving equipment and waterproof cameras. They made films and televisions shows and wrote books so they could share what they learned.